2000
DOI: 10.1002/(sici)1099-0690(200004)2000:8<1589::aid-ejoc1589>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Reactivity of a 2-Azaallenium and of a 2-Azaallylium Ion

Abstract: The rate constants for the reactions of the 2‐azaallenium ion 1b+, the 2‐azaallylium ion 2a+ and the iminium ion 3+ with different nucleophiles were determined by 1H NMR spectroscopy. By correlation with the Linear Free Enthalpy Relationship (LFER) lg k20°C = s (E + N), developed by Mayr and Patz, the electrophilicity parameters E(1b+) = ‐3.7, E(2a+) ≈︁ ‐16 and E(3+) = ‐10.43 were obtained. They show that the relative reactivities of these ions are approximately 1012:1:106. Quantum chemical calculations (ab in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Subsequent work focused on individual functional groups but no attempt was made to correlate MAA with Mayr E for both neutral and cationic electrophiles. At higher levels of theory (MP2 and B3LYP), calculated MAAs also correlate linearly with Mayr electrophilicity for other classes of electrophiles: diarylallyl , and azacarbenium ions . Mayr and coworkers have also shown that neutral electrophiles such as ketones, Michael acceptors, and nitroarenes give good linear correlation between calculated MAAs and Mayr E .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Subsequent work focused on individual functional groups but no attempt was made to correlate MAA with Mayr E for both neutral and cationic electrophiles. At higher levels of theory (MP2 and B3LYP), calculated MAAs also correlate linearly with Mayr electrophilicity for other classes of electrophiles: diarylallyl , and azacarbenium ions . Mayr and coworkers have also shown that neutral electrophiles such as ketones, Michael acceptors, and nitroarenes give good linear correlation between calculated MAAs and Mayr E .…”
Section: Introductionmentioning
confidence: 86%
“…At higher levels of theory (MP2 and B3LYP), calculated MAAs also correlate linearly with Mayr electrophilicity for other classes of electrophiles: diarylallyl 6,7 and azacarbenium ions. 8 Mayr and coworkers have also shown that neutral electrophiles such as ketones, 9 Michael acceptors, 10 and nitroarenes 11 give good linear correlation between calculated MAAs and Mayr E. In theory, the common slope of these lines should correlate with 1/s N for a methyl anion. At all levels of theory, the correlation between MAA and Mayr E are linear with similar slopes but it is sobering to see that, even at high levels of theory, different classes of functional groups such as ketones, Michael acceptors, nitroarenes, benzhydryl cations, allyl cations, and azacarbenium ions, fall on different lines, suggesting that it may be impossible to broadly correlate MAA with Mayr E across all of the canonical functional groups in organic chemistry.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Herein, we report a detailed computational study on the Brønsted acid-initiated formal [1,3]-rearrangement of β-substituted ene-aldimines. Based on the recent results, the 2azaallenium [11] -mediated chemical chain reaction as mechanism was proposed, which involved two key steps: i) fragmentation, i. e. initiation, and ii) product formation, i. e. propagation (Figure 1). In order to probe details of this reaction mechanism, density functional theory (DFT) calculations are undertaken focusing on conformational stability and reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report a detailed computational study on the Brønsted acid‐initiated formal [1,3]‐rearrangement of β‐substituted ene‐aldimines. Based on the recent results, the 2‐azaallenium [11] ‐mediated chemical chain reaction as mechanism was proposed, which involved two key steps: i) fragmentation, i. e . initiation, and ii) product formation, i. e .…”
Section: Introductionmentioning
confidence: 99%
“…Although the details of the reaction pathway are still under investigation, we propose a 2-azaallenium-mediated chain reaction mechanism for the chirality transfer based on the experimental and computational studies, which suggest the involvement of two nucleophilic sites of the ene-aldimine, namely imino nitrogen and allylic carbon (Figure ). In the fragmentation step, nitrogen on the ene-aldimine reactant is protonated, as evident from the conformational stability of the ene-aldimine substrates, followed by the protonation of the allyl group.…”
mentioning
confidence: 99%